2021
DOI: 10.1073/pnas.2012685118
|View full text |Cite|
|
Sign up to set email alerts
|

Pathogenic role of delta 2 tubulin in bortezomib-induced peripheral neuropathy

Abstract: The pathogenesis of chemotherapy-induced peripheral neuropathy (CIPN) is poorly understood. Here, we report that the CIPN-causing drug bortezomib (Bort) promotes delta 2 tubulin (D2) accumulation while affecting microtubule stability and dynamics in sensory neurons in vitro and in vivo and that the accumulation of D2 is predominant in unmyelinated fibers and a hallmark of bortezomib-induced peripheral neuropathy (BIPN) in humans. Furthermore, while D2 overexpression was sufficient to cause axonopathy and inhib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 68 publications
(93 reference statements)
1
38
0
Order By: Relevance
“…Moreover, the impairment of axonal transport, which strongly depends on the MT system, is a common molecular target of the neurotoxicity of other classes of chemotherapy drugs, including BTZ 28 , cisplatin 29 and oxaliplatin 30 . Our findings are consistent with reports of a relevant role of tubulin damage in the alteration of axonal integrity and development of CIPN 2 , 7 , 9 . Furthermore, a recent article shows that blocking the motor protein kinesin-5 by co-treatment with monastrol could resolve the neurotoxicity, by alleviating morphological measures of axonal injury in C57BL/6 mice treated with BTZ 31 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the impairment of axonal transport, which strongly depends on the MT system, is a common molecular target of the neurotoxicity of other classes of chemotherapy drugs, including BTZ 28 , cisplatin 29 and oxaliplatin 30 . Our findings are consistent with reports of a relevant role of tubulin damage in the alteration of axonal integrity and development of CIPN 2 , 7 , 9 . Furthermore, a recent article shows that blocking the motor protein kinesin-5 by co-treatment with monastrol could resolve the neurotoxicity, by alleviating morphological measures of axonal injury in C57BL/6 mice treated with BTZ 31 .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, strong evidence of the pathogenic role of delta2 accumulation was recently demonstrated in sensory neurons in in vivo and in vitro studies of BTZ-induced peripheral neuropathy. These changes were found to be related to axonal MT stabilization, mitochondrial energetics impairment, and they are suggested as sufficient and necessary conditions to cause axonopathy with selective alterations of mitochondria motility 9 . In this study, we demonstrated that BTZ and CFZ doses, resulting cytotoxic for multiple myeloma cells and able to inhibit proteasome in the same manner in adult mouse DRG sensory neurons, show in this cellular model the same different neurotoxicity profiles observed in clinical practice.…”
Section: Introductionmentioning
confidence: 89%
“…This dynamic modification cycle has been implicated in cell division (5-8), neurogenesis (9)(10)(11), and heart failure (12)(13)(14)(15). Detyrosinated tubulin also serves as the sole precursor for the irreversible generation of D2-tubulin, which when stimulated through chemotherapeutic agents leads to peripheral neuropathy (16). The removal of tyrosine can be catalyzed by the vasohibins (two paralogs, VASH1 and VASH2) in complex with the essential cofactor small vasohibin-binding protein (SVBP) (10,17) and reversed by the tubulin tyrosine ligase (TTL) (Fig.…”
mentioning
confidence: 99%
“…This led to hypersensitivity and ultimately manifested as a measurable loss of intraepidermal nerve fibers Another fundamental target of CIPN-induced alterations that has been identified in DRG-based models is mitochondria. Several authors have reported a reduction in mitochondrial bioenergetics and motility in DRG models [117,118]. This effect may be due to alterations in DRG neuronal cytoskeleton, often the target of the toxic effect of chemotherapeutic compounds, but also to cytokine production (such as IL-10) triggered by some CIPN agents [117,118].…”
Section: Functional Analysismentioning
confidence: 99%
“…Several authors have reported a reduction in mitochondrial bioenergetics and motility in DRG models [117,118]. This effect may be due to alterations in DRG neuronal cytoskeleton, often the target of the toxic effect of chemotherapeutic compounds, but also to cytokine production (such as IL-10) triggered by some CIPN agents [117,118].…”
Section: Functional Analysismentioning
confidence: 99%